Long non‐coding RNA T‐cell factor 7 in multiple myeloma: A potential biomarker for deteriorated clinical features and poor prognosis. Issue 9 (23rd June 2020) - Zhang, Cui; Chu, Min; Fan, Yingchao; Wu, Liting; Li, Zhumeng; Ma, Xiaoyan; Zhuang, Wenfang
Abstract: Background: This study aimed to investigate the correlation of long non‐coding RNA T‐cell factor 7 (lnc‐TCF7) with clinical features and prognosis in patients with multiple myeloma (MM). Methods: Totally, 216 newly diagnosed symptomatic MM patients and 60 healthy controls (HCs) were enrolled. Bone marrow samples were collected from patients before treatment and from HCs on donation to detect lnc‐TCF7 expression in plasma cells by reverse transcription quantitative polymerase chain reaction. Besides, clinical response, progression‐free survival (PFS), and overall survival (OS) of patients were assessed. Results: Lnc‐TCF7 expression was increased in patients with MM compared with HCs. Lnc‐TCF7 expression was highest in international staging system (ISS) stage III patients, followed by ISS stage II patients, and then ISS stage I patients, while lnc‐TCF7 expression was similar in patients with different immunoglobulin subtypes and Durie‐Salmon stages. Regarding chromosomal abnormalities, lnc‐TCF7 expression positively correlated with t(4; 14) and Del(17p), whereas no correlation of lnc‐TCF7 expression with t(14; 16), 1q21 amplification, Del(13q), or hyperdiploid was observed in patients with MM. Furthermore, lnc‐TCF7 expression positively correlated with serum creatinine, beta‐2‐microglobulin, and lactate dehydrogenase in patients. Besides, lnc‐TCF7 was negatively associated with complete response but not overall response rate in patients. Additionally, patients with lnc‐TCF7 high expression exhibited shorter PFS and OS compared to patients with lnc‐TCF7 low expression. Conclusion: Lnc‐TCF7 might have clinical value in aiding disease management and prognosis prediction of MM.